18-65 YAŞ ARALIĞINDAKİ DEPRESYON TANILI HASTALARDA SAĞLIKLI GRUPLARLA KARŞILAŞTIRILDIĞINDA SERUM KLOTHO, VİTAMİN D, HOMOSİSTEİN DÜZEYLERİ VE BUNLARIN KLİNİK DEĞİŞKENLERLE İLİŞKİSİNİN İNCELENMESİ - GÜLŞEN, SİNEM ÇEÇEN (Fırat Üniveristesi, 2025)
Çalışmamızda 18-65 yaş aralığındaki depresif bozukluğu bulunan 30 hasta ve benzer yaş grubundaki sağlıklı 30 bireyin verileri Temmuz 2022-Mayıs 2023 tarihleri arasında prospektif olarak toplanarak serum ?-klotho, homosistein ve vitamin D düzeyleri karşılaştırılmıştır. Hastalarımızın yaş ortalaması 41,8±12,7 iken kontrol grubunun 36,9±11,1 idi. Hastalarımızın %90'ı kadın, %10'u erkekti. Hastaların vücut kitle indeks ortalaması 27,4±7,0 iken kontrol grubumuzun 23,9±4,6 idi. Hastaların %33,3'ü kontrol grubunda bulunanların ise %53,3'ü bekardı. Hastaların %30'unun gelir durumu düşük, %66,7'sinin orta ve %3,3'ünün yüksek, kontrol grubumuzda olanların %10'unun gelir durumu düşük, %76,7'sinin orta ve %13,3'ünün yüksekti. Hastalarımızın %63,3'ü ortaokul ve altı, %16,7'si lise ve %20'si ise üniversite mezunuyken kontrol grubunun %60'ı ortaokul ve altı, %10'u lise ve %30'u ise üniversite mezunu eğitim seviyesindeydi. Hasta grubunda olanların %43,3'ünün ailesinde psikiyatrik hastalık öyküsü varken kontrol grubunda olanların %20'sinin ailesinde psikiyatrik hastalık öyküsü vardı. Hasta grubumuzun Beck Depresyon Ölçeği ortalama puanı 24,8±9,4, kontrol grubumuzun 5,5±3,7, hasta grubumuzun Beck Anksiyete ölçeği puan ortalaması 20,5±11,2, kontrol grubumuzun 5,5±4,5, hasta grubumuzun Hamilton Depresyon Ölçeği puan ortalaması 18,6±6,7 iken kontrol grubumuzun 1,9±2,2 olarak hesaplandı. Çalışmamızda her iki grup arasında vitamin D ve homosistein düzeyleri arasındaki fark anlamlı çıkmazken, serumda çözünebilir ?-klotho seviyeleri hasta grubumuzda anlamlı şekilde düşük bulundu. Homosistein düzeyleri erkeklerde anlamlı şekilde yüksek bulundu. Her ne kadar çalışmamızda depresyonla sadece ?-klotho düzeyi ilişkisi anlamlı bulunsa da literatürde her üç biyomarkerın depresyon etyopatogenezinde rolünün olduğunu bildiren çok sayıda çalışma mevcuttur. Depresyon gibi psikiyatrik hastalıklarda alt değişkenlerin fazlalığı nedeniyle biyomarkerların rolünün daha iyi anlaşılabilmesi için homojen ve büyük hasta gruplarındaki daha fazla çalışma gereklidir. Anahtar Kelimeler: Depresyon, Klotho, Vitamin D, Homosistein

In our study, data from 30 patients aged between 18-65 years with depression and 30 healthy individuals in a similar age group were prospectively collected between July 2022 and May 2023, and their serum ?-klotho, homocysteine, and vitamin D levels were compared. The mean age of the patients was 41.8±12.7, while the mean age of the control group was 36.9±11.1. Among the patients, 90% were female and 10% were male. The average body mass index (BMI) of the patients was 27.4±7.0, whereas it was 23.9±4.6 in the control group. In terms of marital status, 33.3% of the patients and 53.3% of the control group were single. Regarding income levels, 30% of the patients had a low income, 66.7% had a medium income, and 3.3% had a high income, while in the control group, 10% had a low income, 76.7% had a medium income, and 13.3% had a high income. In terms of education level, 63.3% of the patients had an education level of middle school or below, 16.7% were high school graduates, and 20% were university graduates, while in the control group, 60% had an education level of middle school or below, 10% were high school graduates, and 30% were university graduates. A psychiatric family history was present in 43.3% of the patients, compared to 20% in the control group. The patients' mean Beck Depression Inventory (BDI) score was 24.8±9.4, while it was 5.5±3.7 in the control group. The mean Beck Anxiety Inventory (BAI) score of the patients was 20.5±11.2, compared to 5.5±4.5 in the control group. The mean Hamilton Depression Rating Scale (HDRS) score of the patients was 18.6±6.7, while it was 1.9±2.2 in the control group. In our study, although no significant differences were found between the two groups in terms of vitamin D and homocysteine levels, serum soluble ?-klotho levels were found to be significantly lower in the patient group. Homocysteine levels were significantly higher in males. Although our study found a significant association between depression and only ?-klotho levels, numerous studies in the literature report the roles of all three biomarkers in the etiopathogenesis of depression. Due to the high variability of subvariables in psychiatric disorders such as depression, further studies with larger and more homogeneous patient groups are needed to better understand the role of biomarkers. Keywords: Depression, Klotho, Vitamin D, Homocysteine
Serum clotho, vitamin D, homocysteine levels and their relationship with clinical variables in patients with depression aged 18-65 years compared with healthy groups
Keywords: Psikiyatri